(3GdYeOI aj Gdabg GdMfHdj (B/s - (3GHf bOGeI, YHO Gddg Hf CMeO,s 541-620 (3g`(B.s; (3GdegOj , YHO GdQRGbs ((3HjQhJ (B:s (3OGQ GdcJGH GdYQHj ,s, 2004)
(3jJfGhd GdCMcGe GdNGUI HGdePgH GdMfHdj(B.s
(3cTGaGJ (B: (3U(B. 155-164.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B.s
(3HHdjhLQGajI (B: (3U(B. 165-168.s
Keywords: (3Gdabg GdMfHdjs; (3Gdabg GdESdGejs -- (3ePGgHs